DNA recovery and analysis from helmeted hornbill (Rhinoplax vigil) casques and its potential application in wildlife law enforcement - Kanita Ouitavon; Ross McEwing; Kitichaya Penchart; Khanitha Sri-aksorn; Vijak Chimchome (Forensic Science International: Animals and Environments, 2022)
Since 2011 the demand from China for the keratin casque from helmeted hornbills, so called red ivory, has increased significantly according to recent studies and has the potential to drive this species to extinction. Wildlife DNA Forensics is the field of science tasked not with expanding academic knowledge but with providing evidence for court in relation to wildlife crimes or for providing robust intelligence information to enforcement agencies in relation to trade routes for illegal wildlife products. In this pilot study, we examine the potential to recover DNA from the casques of the helmeted hornbill and evaluate how this genetic information could be used to better inform investigations into the illegal trade of helmeted hornbills.